HUBUNGAN RESPON TIME DENGAN PERUBAHAN KESADARAN PADA PASIEN CEDERA DI IGD RUMAH SAKIT BHAYANGKARA MAKASSAR - Sinta Wisma Sari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The nurse's response time is the speed in handling the patient, calculated from the time the patient arrives until he gets treatment and one of the factors that affects the emergency patient's survival is the nurse's response time. This study aims to determine the relationship between nurse response time and patient emergency survival at the Emergency Room at Bhayangkara Hospital Makassar. This study used an analytic observational design with a prospective cohort approach. The sampling technique is nonprobability sampling with a total sample of 45 respondents taken by purposive sampling method. The results of this study indicate that the nurse's response time was fast with survival patients as many as 32 (71.1%) respondents and not survival as many as 1 (2.2%) respondents. Meanwhile, the nurse's response time was slow, with 7 (15.6%) patients not surviving and 5 (11.1%) surviving. This study shows that there is a relationship between nurse response time and patient emergency survival at the Bhayangkara Hospital Emergency Room in Makassar with a significance value of p = 0.000 p